Inhibition of methane production in an alpine wetland of the Tibetan plateau by carbon-based nanomaterials - Chengfang Ma; Rong Wen; Miao Lin; Hongfei Chi; Meiling Feng; Pengfei Liu (Environmental Research, 2026)

Decoupling predictors of arbuscular mycorrhizal fungal α- and β-diversity: Plant phylogeny versus functional traits in an alpine artificial grassland of Three-River Source Region - Guoxi Shi; Yingli Ma; Ning Wu; Meiling Guo; Xinchuang Wang; Yongjun Liu; Huyuan Feng; Huakun Zhou; Buqing Yao (Applied Soil Ecology, 2026)

Characteristics of the microbial carbon pump in kelp farming areas and the impact of artificial reefs: A metagenomic and ecological perspective - Junyang Ma; Jihua Liu; Zhansheng Guo; Meiling Zhu; Zitong Chai; Feng Jiang; Zhu Li; Zhenlin Liang; Zhaoyang Jiang (Environmental Research, 2026)

A bacteriohopanetetrol stereoisomer in Western Pacific oxycline indicates anammox-driven nitrogen loss and warm eddy dynamics - Liqin Duan; Jinming Song; Meiling Yin; Xiaowei Wang; Chuanyu Liu; Jiawei Kan; Zhuoyue Wang; Feng Zhao; Xuegang Li; Huamao Yuan (Geochimica et Cosmochimica Acta, 2026)

Porous Eu-ox metal–organic framework enabling open-channel carrier transport and durable Pb2+ immobilization in perovskite solar cells - Zhihang Zhang; Xiaolong Cao; Tiantian Lv; Zhengyan He; Haiyan Sun; Hai Zhong; Qi Zhang; Changlin Yao; Wen Li; Shufang Zhang; Meiling Feng (Chemical Engineering Journal, 2026)

Metagenomic and metatranscriptomic characterization of syntrophic propionate- and butyrate-oxidizing bacterial communities in Qiangyong proglacial lake sediments on the Qinghai-Tibet Plateau - Rong Wen; Hongfei Chi; Meiling Feng; Yang Zhao; Chengfang Ma; Keshao Liu; Qi Yan; Pengfei Liu (Soil Ecology Letters, 2026)

An Ultrasensitive 1,2,3-Triazole Schiff-Based Fluorescence Probe for the Detection of Al3+ and Developing Application of Biological Activity - Chunyang Liu; Junfeng Chen; Xun Kang; Meiling Le; Huajie J. Feng; Wenying Y. He (Journal of Fluorescence, 2026)

Monsoonal intensity dominated the Eocene evolution of paleovegetation and paleoclimate in northern South China Sea - Jinhua Zeng; Tao Jiang; Keqiang Wu; Desheng Hu; Yong Man; Licheng Cao; Cong Cheng; Zigui Chen; Kun Wang; Nan Bai; Meiling Feng; Ziyi Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Spatiotemporal variation of forest water conservation based on dual-variable calibration of runoff and evapotranspiration with SWAT model - Jiao Chen; Meiling Zheng; Feng Lin; Xingwei Chen; Huaxia Yao (Agricultural and Forest Meteorology, 2025)

Different impacts of temperature and precipitation on vegetation net primary production of global marsh wetlands - Jiaqi Zhang; Meiling Zhao; Rong Ma; Mingming Feng; Chen Ding; Liyuan Wu; Xianguo Lu; Xiangjin Shen; Ming Jiang (Global and Planetary Change, 2025)

Large-scale mapping and uncertainty assessment of dominant tree species in southern China based on Sentinel-2 time series - Ben Yang; Yuxin Zhao; Junji Li; Meiling Liu; Lei Feng; Botian Zhou; Ling Wu (Journal of Environmental Management, 2025)

Surface engineering of copper peroxide nanodots and Au nanozyme on porphyrin-based metal-organic frameworks induces cascade reactions for colorectal cancer treatment - Haoyu Chen; Rong Liu; Jiaxin Fu; Xiaohan Zhang; Xiaohua Zhu; Mingjie Wei; Feng Liu; Peng Yin; Haitao Li; Youyu Zhang; Meiling Liu; Juewen Liu (Chemical Engineering Journal, 2025)

Towards robust partial nitrification in low-ammonia wastewater: Electrospinning nanofiber composite-enhanced hydrogel beads immobilized comammox Nitrospira - Peng Tang; Liangang Hou; Meiling Yin; Feng Huang; Zhengwei Pan; Tianhao Shi; Jun Li; Yuhan Zhu; Xin Zhang; Peng Gao (Bioresource Technology, 2025)

Calcium isotope composition of the Gangdese continental arc deep crust and implications for making continental crust - Meiling Wang; Zaicong Wang; Liang Guo; Zongqi Zou; Fei Wu; Wei Dai; Jingliang Guo; Kang Chen; Lanping Feng; Haihong Chen; Ming Li; Yongsheng Liu (Geochimica et Cosmochimica Acta, 2025)

The distribution of nutrients and chlorophyll-a in the temperate coast of China: implications for marine ecological risks in the context of global warming - Dapeng Bai; Hongxian Chu; Yongcai Feng; Lixin Wang; Meiling Yin (Frontiers in Marine Science, 2025)
Introduction Nutrients directly regulate the level of primary productivity, which is crucial for the stability of marine ecosystems. However, under the context of human activities leading to global warming, factors influencing alterations in coastal nutrient dynamics remain a mystery. Methods A study was conducted to investigate the spatial distribution characteristics of nutrients and chlorophyll-a at 55 stations in the Bohai Bay region during the autumn of 2021. Results The dominant factor influencing coastal zone ecology in the surveyed area was identified as temperature. Multiple factors (e.g., riverine input, sediment release, atmospheric deposition, and hydrodynamics) collectively impacted nutrient dynamics. The temperature along the north-south transect was consistent, with a distinct demarcation at 118.68°E (19°C), where the temperature gradient exhibited a pronounced east-high, west-low pattern. The temperature difference between the surface and bottom waters was minimal. In the high-temperature eastern region, the redox potential was high (above 100 mV), and very few locations had low dissolved oxygen levels, indicating active aerobic microbial activity. This led to the decomposition of substantial organic matter, resulting in elevated ammonia-nitrogen concentrations, and low pH levels. The presence of ammonia-nitrogen promoted the growth and reproduction of planktonic organisms. Discussion Therefore, we are concerned that global climate warming may trigger changes, and even worsen, marine ecological environments in temperate coastal regions, necessitating heightened attention from researchers.

Correction to: Metanephric mesenchyme-derived Foxd1+ mesangial precursor cells alleviate mesangial proliferative glomerulonephritis - Meiling Jin; Zhong Yin; Kai Wei; Yuansheng Xie; Xueyuan Bai; Bo Fu; Zhe Feng; Qinggang Li; Xiangmei Chen (Journal of Molecular Medicine, 2025)

Acrylamide drives amidase-mediated gut dysbiosis to aggravate colitis - Daotong Li; Yinghua Luo; Huimin Fan; Li Dong; Xiaoying Zhang; Yu Feng; Meiling Tian; Shuqing Zhang; Wenjing Chen; Lujia Zhang; Jianwei Gao; Xiangning Ma; et al. (Science Bulletin, 2025)

Highly selective capture of Ni2+ from complex environments by a sandwich-like layered metal sulfide ion exchanger - Mingdong Zhang; Qisheng Hong; Yuan Aocheng; Yan Zhang; Xiaoying Huang; Meiling Feng; Jingli Mu (Journal of Hazardous Materials, 2025)

Paleoenvironmental evolution and East Asian monsoon records through three stages of paleochannels since the mid-pleistocene in the Western Bohai Sea, North China - Shuyu Wu; Jun Liu; Hongxian Chu; Yongcai Feng; Meiling Yin; Lixin Pei (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

The role of HMGB2 in the immune response of Nile tilapia (Oreochromis niloticus) to streptococcal infection - Yuhang Dong; Zhiqiang Zhang; Yongxiong Huang; Xuyan Tan; Xing Li; Meiling Huang; Jiaming Feng; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2024)

The immune function of heme oxygenase-1 (HO-1) from Nile tilapia (Oreochromis niloticus) in response to bacterial infection - Jiamin Feng; Yongxiong Huang; Meiling Huang; Xing Li; Kwaku Amoah; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2024)

Correction to: Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)

Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)
Although the functions of programmed death-1 (PD-1) on αβ T cells have been extensively reported, a role for PD-1 in regulating γδT cell function is only beginning to emerge. Here, we investigated the phenotypic and functional characteristics of PD-1-expressing γδT cells, and the molecular mechanism was also explored in the Plasmodium yoelii nigeriensis ( P. yoelii NSM)-infected mice . Flow cytometry and single-cell RNA sequencing (scRNA-seq) were performed. An inverse agonist of RORα, SR3335, was used to investigate the role of RORα in regulating PD-1 + γδT cells. The results indicated that γδT cells continuously upregulated PD-1 expression during the infection period. Higher levels of CD94, IL-10, CX3CR1, and CD107a; and lower levels of CD25, CD69, and CD127 were found in PD-1 + γδT cells from infected mice than in PD-1 − γδT cells. Furthermore, GO enrichment analysis revealed that the marker genes in PD-1 + γδT cells were involved in autophagy and processes utilizing autophagic mechanisms. ScRNA-seq results showed that RORα was increased significantly in PD-1 + γδT cells. GSEA identified that RORα was mainly involved in the regulation of I-kappaB kinase/NF-κB signaling and the positive regulation of cytokine production. Consistent with this, PD-1-expressing γδT cells upregulated RORα following Plasmodium yoelii infection. Additionally, in vitro studies revealed that higher levels of p-p65 were found in PD-1 + γδT cells after treatment with a RORα selective synthetic inhibitor. Collectively, these data suggest that RORα-mediated attenuation of NF-κB signaling may be fundamental for PD-1-expressing γδT cells to modulate host immune responses in the spleen of Plasmodium yoelii nigeriensis –infected C57BL/6 mice, and it requires further investigation.

Validation of endogenous U6 promoters for expanding the CRISPR toolbox in Nicotiana tabacum - Pan Luo; Siyuan Li; Lulu Li; Yanyan Li; Ying Qiao; Xianzhi Wu; Meiling Wu; Zhihao Song; Yong Yang; Ji Feng; Xingchun Tang (In Vitro Cellular & Developmental Biology - Plant, 2024)

All-in-one treatment: Capture and immobilization of 137Cs by ultra-stable inorganic solid acid materials HMMoO6·nH2O (M = Ta, Nb) - Zhihua Chen; Shaoqing Jia; Haiyan Sun; Junhao Tang; Yanling Guo; Yuexin Yao; Tianyu Pan; Meiling Feng; Xiaoying Huang (Water Research, 2024)

STAT2 negatively regulates RIG-I in the antiviral innate immunity of black carp - Ji Liu; Chushan Dai; Lijun Yin; Xiao Yang; Jun Yan; Meiling Liu; Hui Wu; Jun Xiao; Weiguang Kong; Zhen Xu; Hao Feng (Fish & Shellfish Immunology, 2024)

Illuminated fulvic acid stimulates denitrification and As(III) immobilization in flooded paddy soils via an enhanced biophotoelectrochemical pathway - Yanqiong Zeng; Honghui Wang; Jiehua Hu; Jing Zhang; Feng Wang; Tongyu Wang; Qiqi Zhou; Randy A. Dahlgren; Meiling Gao; Hui Gao; Zheng Chen (Science of The Total Environment, 2024)

Anaerobic granular sludge performance in an expanded granular sludge bed reactor treating calcium-rich wastewater by adjusting CaCO3 crystallization: Effect of upflow velocity and Ca2+ concentration - Xiaoji Liu; Dongning Pan; Quan Yuan; Xiyuan Feng; Meixuan Li; Xuening Song; Meiling Li; Yajuan Ge; Yukun Xing; Yuanzhou Yu; Zhengyu Jin (Science of The Total Environment, 2024)

Calcium isotopic compositions of eclogite melts and negligible modification during reaction with lithospheric mantle - Zongqi Zou; Zaicong Wang; Xiao-Jun Wang; Yi-Gang Xu; Li-Hui Chen; Meiling Wang; Lanping Feng; Ming Li; Yongsheng Liu (Geochimica et Cosmochimica Acta, 2024)

Molecular characteristics and functional analysis of non-specific cytotoxic cell receptor (NCCRP1) in golden pompano (Trachinotus ovatus) - Meiling Huang; Zhiqiang Zhang; Xing Li; Jiamin Feng; Yongxiong Huang; Amoah Kwaku; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2024)

Black carp LGP2 suppresses RIG-I mediated IFN signaling during the antiviral innate immunity - Yixuan He; Ji Liu; Yujia Miao; Meiling Liu; Hui Wu; Jun Xiao; Hao Feng (Fish & Shellfish Immunology, 2023)

Apolipoprotein Eb (On-ApoEb) protects Oreochromis niloticus against Streptococcus agalactiae infection - Jiamin Feng; Yongxiong Huang; Meiling Huang; Xing Li; Kwaku Amoah; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2023)

Interleukin-8 involved in Nile Tilapia (Oreochromis niloticus) against bacterial infection - Xing Li; Baijian Jiang; Zhiqiang Zhang; Meiling Huang; Jiamin Feng; Yongxiong Huang; Kwaku Amoah; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2023)

A new S-scheme heterojunction of 1D ZnGa2O4/ZnO nanofiber for efficient photocatalytic degradation of TC-HCl - Wenhui Chen; Tianxin Kang; Fenqi Du; Peipei Han; Meiling Gao; Peng Hu; Feng Teng; Haibo Fan (Environmental Research, 2023)

A novel perlucin-like protein (PLP) protects Litopenaeus vannamei against Vibrio harveyi infection - Jiamin Feng; Yongxiong Huang; Meiling Huang; Junliang Luo; Liwen Que; Shiping Yang; Jichang Jian (Fish & Shellfish Immunology, 2023)

Subducted carbonates not required: Deep mantle melting explains stable Ca isotopes in kimberlite magmas - Michael A. Antonelli; Andrea Giuliani; Zaicong Wang; Meiling Wang; Lian Zhou; Lanping Feng; Ming Li; Zhaofeng Zhang; Fang Liu; Russell N. Drysdale (Geochimica et Cosmochimica Acta, 2023)

Negatively regulation of MAVS-mediated antiviral innate immune response by E3 ligase RNF5 in black carp - Jun Yan; Guoxia Qiao; Enhui Wang; Yuqing Peng; Jiamin Yu; Hui Wu; Meiling Liu; Jiagang Tu; Yongan Zhang; Hao Feng (Fish & Shellfish Immunology, 2023)

Plant Growth Regulators Enhance Saline–Alkali Tolerance by Upregulating the Levels of Antioxidants and Osmolytes in Soybean Seedlings - Minglong Yu; Qiong Wu; Dianfeng Zheng; Naijie Feng; Xilong Liang; Meiling Liu; Yao Li; Baomin Mou (Journal of Plant Growth Regulation, 2022)

Comparative transcriptome analysis of global effect of ddh and lysE deletion on 4-hydroxyisoleucine production in Corynebacterium glutamicum - Rui Chen; Youhe Xiang; Xinping Yu; Meiling Zhang; Feng Shi (Systems Microbiology and Biomanufacturing, 2022)

Bentazone in water and human urine in Wuhan, central China: exposure assessment - Pei Wang; Meiling Cao; Feng Pan; Junling Liu; Yanjian Wan; Huaiji Wang; Wei Xia (Environmental Science and Pollution Research, 2022)

Liver kinase B1 (LKB1) reduced inflammation and oxidative stress by regulating the AMPK/NLRP3 signaling pathway in LPS-induced lung injury - Yifeng Yue; Liwu Zong; Yongmin Chen; Nianhai Feng; Junxia Tang; Hongyu Xu; Meiling Zhao (Molecular & Cellular Toxicology, 2021)

A new parametric segmentation method based on sandy mudstone SEM images - Meiling Zhou; Jianlin Li; Weijie Xu; Feng Xu; Eleyas Assefa; Huafeng Deng (Arabian Journal of Geosciences, 2021)

Ternary catalyst Mn-Fe-Ce/Al2O3 for the ozonation of phenol pollutant: performance and mechanism - Manning Zhang; Dulin Yin; Jinjin Guo; Huanghe Wu; Meiling Gong; Xiangdong Feng (Environmental Science and Pollution Research, 2021)

Retraction Note to: Explore on the effect of ATF6 on cell growth and apoptosis in cartilage development - Xiaofeng Han; Peng Zhang; Rong Jiang; Fei Xia; Meiling Li; Feng‑Jin Guo (Histochemistry and Cell Biology, 2020)

Molecular evidence of goose-parvovirus-related abnormal molting in Pekin ducks - Meiling Jin; Chonglun Feng; Xiaoyan Wang; Dabing Zhang (Archives of Virology, 2019)

Metanephric mesenchyme-derived Foxd1+ mesangial precursor cells alleviate mesangial proliferative glomerulonephritis - Meiling Jin; Zhong Yin; Kai Wei; Yuansheng Xie; Xueyuan Bai; Bo Fu; Zhe Feng; Qinggang Li; Xiangmei Chen (Journal of Molecular Medicine, 2019)

Combination of NAD+ and NADPH Offers Greater Neuroprotection in Ischemic Stroke Models by Relieving Metabolic Stress - Qiao Huang; Meiling Sun; Mei Li; Dingmei Zhang; Feng Han; Jun Chao Wu; Kohji Fukunaga; Zhong Chen; Zheng-Hong Qin (Molecular Neurobiology, 2018)

Long noncoding RNAs in the mTOR signaling network: biomarkers and therapeutic targets - Tinglei Huang; Meiling Wang; Bo Huang; Augustus Chang; Feng Liu; Yanjie Zhang; Bin Jiang (Apoptosis, 2018)

Akt Inhibitor Perifosine Prevents Epileptogenesis in a Rat Model of Temporal Lobe Epilepsy - Feng Zhu; Jiejing Kai; Linglin Chen; Meiling Wu; Jingyin Dong; Qingmei Wang; Ling-Hui Zeng (Neuroscience Bulletin, 2018)

Comparative genomic analysis of three white spot syndrome virus isolates of different virulence - Fang Li; Meiling Gao; Limei Xu; Feng Yang (Virus Genes, 2017)

Abnormal Functional Connectivity Density in Post-traumatic Stress Disorder - Youxue Zhang; Bing Xie; Heng Chen; Meiling Li; Feng Liu; Huafu Chen (Brain Topography, 2016)

Endogenous level of TIGAR in brain is associated with vulnerability of neurons to ischemic injury - Lijuan Cao; Jieyu Chen; Mei Li; Yuan-Yuan Qin; Meiling Sun; Rui Sheng; Feng Han; Guanghui Wang; Zheng-Hong Qin (Neuroscience Bulletin, 2015)

Integrating Genome-Wide Association Study and Brain Expression Data Highlights Cell Adhesion Molecules and Purine Metabolism in Alzheimer’s Disease - Zimin Xiang; Meiling Xu; Mingzhi Liao; Yongshuai Jiang; Qinghua Jiang; Rennan Feng; Liangcai Zhang; Guoda Ma; Guangyu Wang; Zugen Chen; Bin Zhao; Tiansheng Sun; et al. (Molecular Neurobiology, 2015)

Characterization of Post-traumatic Stress Disorder Using Resting-State fMRI with a Multi-level Parametric Classification Approach - Feng Liu; Bing Xie; Yifeng Wang; Wenbin Guo; Jean-Paul Fouche; Zhiliang Long; Wenqin Wang; Heng Chen; Meiling Li; Xujun Duan; Jiang Zhang; Mingguo Qiu; et al. (Brain Topography, 2015)

RETRACTED ARTICLE: Explore on the effect of ATF6 on cell growth and apoptosis in cartilage development - Xiaofeng Han; Peng Zhang; Rong Jiang; Fei Xia; Meiling Li; Feng-Jin Guo (Histochemistry and Cell Biology, 2014)

Classification of densities and characteristics of curve of population centers in China by GIS - Meiling Ge; Zhiming Feng (Journal of Geographical Sciences, 2010)